Plasma Cardiotrophin-1 as a Marker of Hypertension and Diabetes-Induced Target Organ Damage and Cardiovascular Risk. Issue 30 (July 2015) - Gamella-Pozuelo, Luis; Fuentes-Calvo, Isabel; Gómez-Marcos, Manuel A.; Recio-Rodriguez, José I.; Agudo-Conde, Cristina; Fernández-Martín, José L.; Cannata-Andía, Jorge B.; López-Novoa, José M.; García-Ortiz, Luis; Martínez-Salgado, Carlos; Hsueh, Wang.
<x xml:space="preserve">Abstract</x> Abstract The search for biomarkers of hypertension and diabetes-induced damage to multiple target organs is a priority. We analyzed the correlation between plasma cardiotrophin-1 (CT-1), a chemokine that participates in cardiovascular remodeling and organ fibrosis, and a wide range of parameters currently used to diagnose morphological and functional progressive injury in left ventricle, arteries, and kidneys of diabetic and hypertensive patients, in order to validate plasma levels of CT-1 as clinical biomarker. This is an observational study with 93 type 2-diabetic patients, 209 hypertensive patients, and 82 healthy controls in which we assessed the following parameters: plasma CT-1, basal glycaemia, systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), left ventricular hypertrophy (LVH by electrocardiographic indexes), peripheral vascular disease (by pulse wave velocity—PWV, carotid intima-media thickness—C-IMT, and ankle-brachial index—ABI), and renal impairment (by microalbuminuria, albumin/creatinine urinary ratio, plasma creatinine concentrations, and glomerular filtration rate). Hypertensive or diabetic patients have higher plasma CT-1 than control patients. CT-1 positively correlates with basal glycaemia, SBP, DBP, PP, LVH, arterial damage (increased IMT, decreased ABI), and early renal damage (microalbuminuria, elevated albumin/creatinine ratio). CT-1 also correlates with increased 10-year cardiovascular risk. Multiple linear regression analysis confirmed that CT-1 was associated with arterial injury assessed by PWV, IMT, ABI, and cardiac damage evaluated by Cornell voltage duration product. Increases in plasma CT-1 are strongly related to the intensity of several parameters associated to target organ damage supporting further investigation of its diagnostic capacity as single biomarker of cardiovascular injury and risk and, possibly, of subclinical renal damage.